Association between diffuse idiopathic skeletal hyperostosis and thoracic kyphosis in patients with cervical myelopathy: a retrospective observational study - Motoyoshi Takayuki (BMC, 2021)
Abstract Background Diffuse idiopathic skeletal hyperostosis (DISH) is a structural abnormality of the thoracic spine that is known to impair posture. However, the relationship between DISH and sagittal balance in the whole spine is unclear. The aims of this study were to investigate the prevalence of DISH in patients with cervical myelopathy caused by cervical ossification of the posterior longitudinal ligament (OPLL) or cervical spondylosis and to compare sagittal alignment of the spine between patients with and without DISH. Methods A total of 103 consecutive patients with a diagnosis of cervical myelopathy due to cervical OPLL or spondylosis were retrospectively enrolled in this single-center study. DISH was defined as an ossified lesion that was seen to be completely bridging at least four contiguous adjacent vertebral bodies in the thoracic spine on computed tomography scans. Cervical and spinopelvic sagittal parameters were measured in whole spine radiographs. Results The study population included 28 cases with DISH [DISH (+) group] and 75 without DISH [DISH (−) group]. OPLL was more prevalent in the DISH (+) group than in the DISH (−) group; however, there were no significant differences in other clinical findings. Propensity score matching produced 26 pairs. C7 slope, C2-7 sagittal vertical axis (C-SVA), whole thoracic kyphotic angles, upper thoracic kyphosis, and T5-T12 thoracic kyphosis values were significant higher in the DISH (+) group than in the DISH (−) group. There was no significant between-group difference in the other sagittal spinopelvic parameters. Conclusions This study is the first to compare sagittal alignment in patients with cervical myelopathy according to whether or not they have DISH. Patients with DISH are more likely to have excessive kyphosis in the thoracic spine, a high C7 slope, and a high C2-7 SVA.